Efektifitas Reinforcement Positif Terhadap Keaktifan Siswa Kelas VI Pada Mata Pelajaran Tematik di SD Muhammadiyah 14 Surabaya - Galuh Candra Ningrum; Ilham Yusril; Yesi Septiana; Danieltus Nen; Starry Kireida Kusnadi (Fakultas Psikologi Universitas Wijaya Putra, 2022)
Education is one of the important things in development a country. To be able to improve the quality of education, the government has made various efforts, including through improving educational facilities and infrastructure, various kinds of training to improve teacher competence, and changing the education curriculum on a regular basis, this is done so that it has a positive impact on improving the quality of education (in Andriyani, Yesi, 2018). Students are those who are specifically submitted by parents to take part in learning at schools with the aim of becoming human beings who have knowledge, skills, experience, personality, character and independence (in Ali, 2010). In this study, there were 296 students at Muhammadiyah 14 Elementary School in Surabaya with details of 165 male students and 131 female students. Class 6 has 49 students who are divided into 2 classes,25 students are in class 6A and 24 students in class 6B. Using research methods in theform of experiments where the effect of manipulation on the dependent variable is then measured after the treatment (in Sukma 2014). This research is One-Group Pretest Posttest Design. Where this research can be useful to provide information about the relationship between reinforcement and student activity.